When is it best to discontinue diazoxide in children with persistent hyperinsulinaemic hypoglycaemia and negative genetics for KATP channel gene variants?. (28th August 2021) - Güemes, Maria; Kostopoulou, Eirini; AlYahyaei, Mouza; Gilbert, Clare; Shah, Pratik
Abstract: Diazoxide is the first‐line treatment in children with hyperinsulinaemic hypoglycaemia (HH); however, limited information is available on the duration of diazoxide treatment in children who require over 2 years of it. Hence, we retrospectively reviewed the clinical and biochemical aspects, as well as the duration of therapy and neurodevelopmental assessment, in genetically uncharacterised diazoxide‐responsive HH patients admitted to a tertiary hospital over the last 16 years, who had successfully discontinued diazoxide and remained euglycaemic. To exclude transient HH forms, only patients that required diazoxide for over 2 years were studied. We identified a total of 17 patients (70% males), in whom HH was diagnosed between 1 day and 18 months of age, and 88% were born at term with a median birth weight of 3.79 kg. All children responded to diazoxide at a median dose of 11.5 mg/kg/day, and it was stopped at a median age of 8.5 years, with a median duration of therapy of 7.25 years. The cases that required diazoxide the longest manifested no specific biochemical or clinical characteristics. Fasting tests performed after diazoxide discontinuation showed no longer requirement of diazoxide in all the cases. A total of 64.7% of the children showed mild to moderate developmental delay. Therefore, it seems that long‐term resolution of HH in children with negative genetics for KATP channel genes who required diazoxide for over 2 years will ensue, and thus regular evaluation is crucial. The possible molecular mechanisms involved are unclear.